Skybox Schools: Public Education As Private Luxury - Laurie Reynolds (Washington University Law Quarterly, 2004)
For the past three decades, plaintiffs in hundreds of state and federal court lawsuits have challenged state laws that fund public schools with the local property tax. As socioeconomic segregation remains at extremely high levels across the country, reliance on a tax that is based on the wealth of the property within a school district’s territory produces huge inequality in revenues. As the result of numerous court opinions, legislative reforms, and public pressure, many states have revised their funding formula to shift some of the burden to the state level. However, notwithstanding the wide-ranging statutory amendments and increased state funding, the tremendous gap between wealthy and poor districts remains. In some cases the gap has increased, even in many of those states whose highest courts have invalidated their school finance statutes. This Article asserts that this entrenched inequality stems from two related facts: first, that the local property tax remains the single most important source of public school dollars; and second, that most state finance reforms have left untouched the ability of school districts to raise as much money from the local property tax as the district’s property owners will tolerate. This Article considers the insights of Professor Robert Frank’s book Luxury Fever and explores the spending patterns of wealthy school districts. It concludes, much like Frank concluded in his analysis of the private consumer market, that unchecked taxing and spending powers have created a pattern of luxury spending by the nation’s wealthy school districts. It then evaluates, and rejects, the arguments used by those who support the preservation of unlimited local taxing discretion. Subsequent sections describe the statutory schemes of those few states that have purported to implement caps, showing how the caps themselves typically contain so many exemptions and exceptions that they fail to impose a real limit on wealthy district spending. Suggesting that it is time to reconsider the widespread support of the local property tax for school funding, this Article concludes by proposing that states completely replace the local property tax with a statewide tax on real property and narrowly limit the ability of wealthy districts to “overspend.” Although the proposals leave unanswered many difficult questions about educational policy and equal school funding, this Article concludes that a cap on school district taxing powers is a fundamental prerequisite to meaningful school finance reform.
Keywords: Education – Finance; Property tax; Equal education; Luxury taxes